Benzimidazole derivatives as potential dual inhibitors for PARP-1 and DHODH. Issue 15 (1st August 2015) - Abdullah, Iskandar; Chee, Chin Fei; Lee, Yean-Kee; Thunuguntla, Siva Sanjeeva Rao; Satish Reddy, K.; Nellore, Kavitha; Antony, Thomas; Verma, Jitender; Mun, Kong Wai; Othman, Shatrah; Subramanya, Hosahalli; Rahman, Noorsaadah Abd.
Graphical abstract: Abstract: Poly (ADP-ribose) polymerases (PARPs) play diverse roles in various cellular processes that involve DNA repair and programmed cell death. Amongst these polymerases is PARP-1 which is the key DNA damage-sensing enzyme that acts as an initiator for the DNA repair mechanism. Dihydroorotate dehydrogenase (DHODH) is an enzyme in the pyrimidine biosynthetic pathway which is an important target for anti-hyperproliferative and anti-inflammatory drug design. Since these enzymes share a common role in the DNA replication and repair mechanisms, it may be beneficial to target both PARP-1 and DHODH in attempts to design new anti-cancer agents. Benzimidazole derivatives have shown a wide variety of pharmacological activities including PARP and DHODH inhibition. We hereby report the design, synthesis and bioactivities of a series of benzimidazole derivatives as inhibitors of both the PARP-1 and DHODH enzymes.